Cyanogenic potential in food crops and its implication in cassava ( Manihot esculenta Crantz) production - Fokunang, C.N.; Tomkins, P.T.; Dixon, Alfred G.O.; Tembe-Fokunang, E.A.; Salwa, B.; Nukenine, E.N.; Horan, I. (Science Alert, 2001)
Cyanide a by-product from cyanogenic glucosides is toxic to humans and most living organisms due to its ability of binding to metals such as iron, zinc and copper functional groups of the ligands of most bio enzymes. The cyanide inhibits the reduction of oxygen in the respiratory electron transfer system, the inhibition of plastocyanin reduction in photosynthesis and catalase activity. The magnitude of cyanide metabolism varies greatly between different plant species. Although most plant species produce small amount of cyanide associated with ethylene production, between 3-12000 plant species produce sufficient amounts of cyanogenic compounds that they may function as translocatable forms of reduced nitrogen or as chemical defense molecules against pests and diseases. This paper discusses the cyanogenic potential (ability to produce hydrogen cyanide), in food crops, the importance of cassava as a cyanogenic food crop, cyanide toxicity, metabolism, the enzyme activities of linamarases ( -glucosidase), hydroxyl nitrile lyase, and cyanide detoxification processes.